The Intersection of Artistic Practice and Research: Exploring the Role of Drawing in Creative Inquiry - Charu Sharma (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Drawing is universally recognized as a fundamental artistic practice, integral to human expression and communication from childhood onward. Despite the academization of the arts posing challenges to creative processes, artistic research remains distinct from traditional scientific methods. It emphasizes the continuous exploration and questioning inherent in artistic practices rather than rigid objectives or methods. Artistic inquiry, as argued by Joseph Kosuth, involves cultivating and explicating conceptual implications, blurring the lines between creation and intellectualization. This approach is exemplified by Fuad Arif’s drawing practice, which focuses on the meaningfulness of the creative process itself rather than seeking definitive formulations or techniques. In artistic research, the artist-researcher becomes the instrument, integrating their tools and methods to engage in a deeper understanding of art. This process-oriented perspective aligns with the notion that art embodies a form of knowledge that is enigmatic and interpretive, challenging the conventional parameters of research. Ultimately, artistic research questions the necessity of predefined directions, procedures, and results, advocating for a more fluid and reflective inquiry into the nature of art.
Keywords: Drawing; Painting; Visual Art; Nature; High-Performance Concrete